Enhancing Accounting Students' Competence through Information Technology-based Financial Reporting: A Community Engagement Initiative in Sidoarjo - Aisha Hanif; Nur Ravita Hanun; Dina Dwi Oktaviarini; Atina Nabila; Binti Nadhifa (Indonesian Journal of Cultural and Community Development, 2023)
In this digital era, the demands for Information and Communication Technology (ICT) have led to the increasing need for accounting students to acquire additional hard skills in operating simple accounting programs like spreadsheets. To address this need, a community engagement program was conducted in partnership with a vocational school in Sidoarjo to provide training on information technology-based financial reporting. The methods included surveys, discussions, problem formulation, planning, demonstrations, and learning evaluation. The program aimed to enhance students' basic knowledge and expertise in accounting, enabling them to compete in the Industrial Revolution era. The outcome of the program showed significant improvement in students' ability to utilize spreadsheets for data processing and financial statement preparation. The success of this initiative highlights the importance of incorporating technology in accounting education to equip students with relevant skills for the modern job market. Highlight: Integration of Information Technology: The study highlights the increasing demand for accounting students to possess skills in utilizing information technology, particularly spreadsheets, for data processing and financial reporting. Community Engagement Approach: The research employs a community engagement initiative to address partners' problems, including surveys, counseling, and providing solutions to enhance students' competencies. Benefits for Accounting Students: The program's main benefit is the enhancement of basic knowledge and expertise of accounting students in Sidoarjo, empowering them to compete effectively in the modern era. Keyword: Information Technology, Accounting Education, Spreadsheet, Financial Reporting, Industrial Revolution